The potent, indirect adenosine monophosphate-activated protein kinase activator R419 attenuates mitogen-activated protein kinase signaling, inhibits nociceptor excitability, and reduces pain hypersensitivity in mice. (July 2016) - Mejia, Galo L.; Asiedu, Marina N.; Hitoshi, Yasumichi; Dussor, Gregory; Price, Theodore J.
Abstract : Abstract: There is a great need for new therapeutics for the treatment of pain. A possible avenue to development of such therapeutics is to interfere with signaling pathways engaged in peripheral nociceptors that cause these neurons to become hyperexcitable. There is strong evidence that mitogen-activated protein kinases and phosphoinositide 3-kinase (PI3K)/mechanistic target of rapamycin signaling pathways are key modulators of nociceptor excitability in vitro and in vivo. Activation of adenosine monophosphate-activated protein kinase (AMPK) can inhibit signaling in both of these pathways, and AMPK activators have been shown to inhibit nociceptor excitability and pain hypersensitivity in rodents. R419 is one of, if not the most potent AMPK activator described to date. We tested whether R419 activates AMPK in dorsal root ganglion (DRG) neurons and if this leads to decreased pain hypersensitivity in mice. We find that R419 activates AMPK in DRG neurons resulting in decreased mitogen-activated protein kinase signaling, decreased nascent protein synthesis, and enhanced P body formation. R419 attenuates nerve growth factor (NGF)-induced changes in excitability in DRG neurons and blocks NGF-induced mechanical pain amplification in vivo. Moreover, locally applied R419 attenuates pain hypersensitivity in a model of postsurgical pain and blocks the development of hyperalgesic priming in response to both NGF and incision. We conclude that R419 is a promising lead candidate compound for the development of potent and specific AMPK activation to inhibit pain hypersensitivity as a result of injury. Abstract : Supplemental Digital Content is Available in the Text.